Description of Pregnant Women's Nutritional Status Based on The Mid-Upper Arm Circumference in Sundari Medan General Hospital In 2019 - Franli, David; Sitepu, Makmur; Pasaribu, Hotma Partogi; Martina, Sake Juli (Sumatera Medical Journal, 2020)
Introduction. Chronic energy deficieny (CED) is a condition of a body characterized by low body weight and low energy stores, possibly limited physical capacity due to deprivation of food over a long period time. Ministry of Health ( Kemenkes) showed that in 2015, 305 out of 100.000 death of pregnant women is realated to malnutriotion and CED. Objective. The aim of this study is to determine the overview of pregnant women nutritional status based on mid-upper arm circumference (MUAC) in Sundari Medan General Hospital. Method. The study was an observational descriptive study with a cross sectional design. The samples of this study consists of pregnant women from Sundari Medan Genaral Hospital, who had fulilled the inclusion and esclusion criteria by total sampling. Results.. Among 60 samples, the prevalance of Non-CED woman (85%) was found higher than the mild malnutrition (15%). Conclusion. Prevalance of CED pregnant women was found higher in risky age, middle educated and high income family.